Professing Contradictions: Knowledge Work and the Neoliberal Condition of Academic Workers - Marco Briziarelli; Joseph L. Flores (tripleC: Communication, Capitalism & Critique)
In this paper, we will provide an interpretation of the condition of academic labor, which is understood as a particular kind of knowledge work and labor. Our objective is to explore the contradictory condition of academics in terms of class position, production of value and subjectivity, showing both its idiosyncrasies as well as its alignment with the broader experience of working in current post-Fordist capitalism. First, paying particular attention to the US media and communication departments that develop critical cultural scholarship, we reflect on the unresolved impasse deriving from the distinction of mental and manual labor. Second, we describe this profession as being characterized by a contradictory class location and a valorization that relies on a continuous negotiation for better exchange rate between intellectual and financial capital. Third, we consider how such a context subjectively translates in an ever-resolved condition of ‘employability,’ which comprises vocational aspects and the necessity dictated by the hope to reach stability and recognition.